2018
DOI: 10.1007/s10886-018-1029-y
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation Resistance and Micro-Climate Adaptation: Cuticular Hydrocarbon Signatures of Different Argentine Ant Supercolonies Across California

Abstract: Cuticular hydrocarbons (CHCs), the dominant fraction of the insects' epicuticle and the primary barrier to desiccation, form the basis for a wide range of chemical signaling systems. In eusocial insects, CHCs are key mediators of nestmate recognition, and colony identity appears to be maintained through a uniform CHC profile. In the unicolonial Argentine ant Linepithema humile, an unparalleled invasive expansion has led to vast supercolonies whose nestmates can still recognize each other across thousands of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 59 publications
(74 reference statements)
4
28
0
Order By: Relevance
“…Our study is the first social insect study to link variation in cuticular hydrocarbons with variation in colony productivity, although previous social insect studies have linked variation in cuticular hydrocarbons to worker survival (Sprenger et al 2018) or to climatic or biotic variation (Menzel et al 2017;Buellesbach et al 2018;Sprenger et al 2018 Interestingly, we found similar linear selection patterns using both definitions, as all significant linear estimates were in the same direction between the two definitions (Figure 3, Supplement table 2). This suggests that the hydrocarbon profile optima are largely aligned for the production of both reproductives and workers in our study population.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our study is the first social insect study to link variation in cuticular hydrocarbons with variation in colony productivity, although previous social insect studies have linked variation in cuticular hydrocarbons to worker survival (Sprenger et al 2018) or to climatic or biotic variation (Menzel et al 2017;Buellesbach et al 2018;Sprenger et al 2018 Interestingly, we found similar linear selection patterns using both definitions, as all significant linear estimates were in the same direction between the two definitions (Figure 3, Supplement table 2). This suggests that the hydrocarbon profile optima are largely aligned for the production of both reproductives and workers in our study population.…”
Section: Discussionsupporting
confidence: 59%
“…), diet, and environmental conditions experienced by the colonies. Such control in particular is valuable given the complexity of social insect colonies (Linksvayer 2006;Kronauer & Libbrecht 2018) and the sensitivity of the hydrocarbon profile to changes in the environment or diet (Francis et al 1989;vander Meer et al 1989;Liang & Silverman 2000;Tissot et al 2001;Buczkowski et al 2005;van Zweden et al 2009;Pavković-Lučić et al 2016;Menzel et al 2017;Buellesbach et al 2018). Although future field studies would be beneficial, in particular to identify how variation in cuticular hydrocarbons affects colony productivity in a natural setting, a field study on a similar scale as our study is likely not feasible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, these changes may reflect a physical response of the CHC blend to dryness rather than a physiological mechanism to control water loss. Indeed, these CHC changes would reduce overall waterproofing, although some authors found that alkenes also increase with temperature [22,52].…”
Section: Discussionmentioning
confidence: 99%
“…Nongenetic factors contributing to CHC diversity could potentially overshadow the detectable impact of individual biosynthesis genes, hampering attempts to fully resolve the explicit contributions of each individual gene. Several studies have revealed a remarkable adaptability of CHC profiles to diverse biotic and abiotic conditions in different insect taxa (e.g., Rajpurohit et al 2017;Buellesbach et al 2018b;Menzel et al 2018). Also, since CHC biosynthesis is linked to the uptake of amino acids (Dillwith et al 1982;Chase et al 1990) and has been shown to be influenced by several metabolic pathways, such as the citric acid cycle and fatty acid synthesis (Barber et al 2005;Blomquist and Bagnères 2010), diet can contribute to variations in CHC profiles as well (e.g., Fedina et al 2012).…”
Section: Phenotypic Plasticity and Nongenetic Factorsmentioning
confidence: 99%